Confusion and seizures: is a CT head always required? - Mohamed Salah Fayed; Isbah Munir; Moez Nayyar (Clinical Medicine)
Introduction: CT head is readily utilised in patients presenting with confusion and seizures. National Institute of Health and Care Excellence (NICE) have published detailed guidance on the use of computed tomography (CT) head in patients with seizures or head trauma. It is not recommended to perform a CT head in patients with epilepsy who present with a typical seizure.1,2 CT head has a low yield in patients presenting with confusion without neurological symptoms.3 Despite the published guidelines, the overuse of CT head remains an ongoing concern.4 We aimed to identify patients who are most likely to benefit from a CT head. Method: We randomly selected 100 patients who presented to the emergency department with confusion or seizures and went on to have a CT head, over a 1-month period. Data, including demographics, history of trauma, presenting complaint, home medications and CT findings, were collected. Results: 51 patients presented with a seizure. 42 (82.4%) had previous history of seizures, 13 (25.5%) had neurological signs, 15 (29.4%) had recent trauma and 4 (7.8%) were on oral anticoagulation. Eight (15.7%) CT head scans showed an acute abnormality; five (62.5%) of these patients had loss of consciousness, one (12.5%) had trauma and three (37.5%) were on anticoagulation. Two (25%) scans showed brain metastases. Both these patients had a history of cancer. One (12.5%) showed meningioma. One (12.5%) showed subdural haemorrhage and subarachnoid haemorrhage because of trauma. Three (37.5%) showed subdural haemorrhage. These three patients were on oral anticoagulants and all had loss of consciousness.46 patients presented with confusion without a seizure. 15 (32.6%) had neurological signs, 24 (52.2%) had trauma, 14 (30.4%) were on oral anticoagulants, eight (17.4%) had history of cancer, nine (19.6%) had hyponatraemia and 12 (26.1%) had an infection. Only three (6.5%) scans showed an acute abnormality: one (33.3%) had subdural haemorrhage because of trauma, one (33.3%) showed a space-occupying lesion and one (33.3%) showed an ischaemic stroke.Overall, 21 patients had an infection. Only one of these had an acute abnormality on CT head. Conclusion: Clinicians should adopt a low threshold for performing CT head in patients on oral anticoagulants when there is history of trauma or loss of consciousness. CT head is unlikely to show an acute abnormality in patients presenting with confusion alone. Confusion and seizures are common during infection and may not warrant a CT head. Careful selection of patients in such a way can avoid unnecessary radiation exposure and also reduce the cost to the NHS.